The digital pedestrian network in complex urban contexts: a primer discussion on typological specifications - Cambra,Paulo Jorge (2019)
A safe and accessible pedestrian network is essential to an equitable and sustainable urban mobility system. The importance and benefits of pedestrian-friendly urban environments has been widely addressed in transport research, yet most studies focusing in pedestrian accessibility use available street network datasets that do not represent effectively the pedestrian environment. In some cases the use of street centrelines can provide a rather good approximation to pedestrian accessibility measures. However, in the context of transportation planning and policy, the use of street centrelines fails to address critical pedestrian concerns, such as road crossing opportunities and accessible infrastructure for all. The variety of street environments and their impact on pedestrian behaviour raises some issues related with network typologies and their representation. In this paper we present and discuss issues arisen from the manual digitization of areas of a case study in Lisbon, Portugal, demonstrating significant differences in the layout of the pedestrian network when addressing different urban contexts. A detailed pedestrian network dataset was built, covering 6 different urban settings, comprising data on formal and informal pedestrian crossings and traversable/inaccessible pathways. Results show that "regular" street layouts are plain in their structure and therefore likely suitable for automated digitization, whilst less conventional street and crossing arrangements or areas with ample public spaces show a network complexity level that still requires human interpretation. The aim of this study is to encourage the discussion on the harmonization of digitization specifications for geographic datasets that can enable realistic analysis of pedestrian accessibility.